The effect of feeding with spoon and bottle on the time of switching to full breastfeeding and sucking success in preterm babies - Aytekin, Aynur (Turk Pediatri Ars, 2014)
AIM: This research was conducted to determine the effect of the feeding methods of spoonfeed and feeding by bottle on the time of switching to full breastfeeding and sucking success. MATERIAL AND METHODS: The study was conducted between September 2013 and January 2014 at the primary level of the neonatal intensive care clinics in two hospitals found in the eastern region of Turkey in a comperative and descriptive fashion. The population was composed of preterm babies who received treatment and care in these clinics during the period when the study was conducted and who met the criteria of the investigators. Without selecting the sample group the whole of the population was studied. The study was conducted with 37 preterm babies who were spoonfed and 35 preterm babies who were fed by bottle. The data were collected with “information form introducing preterm baby”, “follow-up form for preterm baby” and “LATCH Breastfeeding Assessment Tool”. The data were evaluated using percentage distribution, mean, chi-square test, t-test in independent groups, Cronbach alpha coefficient and McNemar analysis. Ethics committee approval was obtained from Atatürk University Faculty of Health Sciences (dated 08.05.2013) and official approvals were obtained from the related hospitals to conduct the study. RESULTS: A significant difference was found between the mean times of switching to full breastfeeding from the first breast-feeding in preterm babies in the spoonfed group and bottle fed group in favour of the spoodfed group (p<0.05). No significant difference was found between the two groups in terms of starting breastfeeding, switching to full breastfeeding, the mean weights at discharge and the mean times of discharge (p>0.05). While no significant difference was found between the groups in terms of mean LATCH scores measured initially (p>0.05), the mean scores in the spoonfed group at the second and final measurement were found to be statistically significantly higher (p<0.05). CONCLUSIONS: It was found that the preterm babies in whom spoonfeeding was used as a supportive method in addition to breast-feeding switched to full breastfeeding in a shorter time compared to the babies who were fed by bottle and their sucking success was at a better level.